Effect of rock composition microstructure and pore characteristics on its rock mechanics properties - Huamin Li; Huigui Li; Kailin Wang; Chuang Liu (International Journal of Mining Science and Technology, 2018)
This paper is to study the influence of composition, microstructure and pore characteristics on the rock mechanical properties. Five kinds of sandstone compositions were analyzed by using X-ray diffraction instrument. And the microstructure was observed by using scanning electron microscope. Then the pore distribution characteristic was investigated by using the low field nuclear magnetic resonance equipment. Finally, the uniaxial compression test was carried out to investigate the mechanical characteristics by using RMT150C mechanics experimental system and the uniaxial compressive strength, Poisson’s ratio and elastic modulus were obtained. Compared to the analysis of the composition, structure and pore distribution and mechanical properties of the five kinds of sandstones, the relationship among composition, structure, pore distribution and mechanical properties was obtained. The results show that the composition, microstructure, pore distribution and mechanical properties of sandstone are closely related. With the decrease of feldspar and quartz particles, the compressive strength and elastic modulus increase, while the porosity decreases. Keywords: Mechanical characteristics, Pore characteristics, Microstructure, Composition, Scanning electron microscope